Contribuição do método geofísico eletromagnético no domínio de tempo para o estudo dos sistemas aquíferos multicamada transfronteiriços da bacia do Kalahari, Cunene, Angola - Francés, Alain Pascal (2023)
SUMMARY: Under the scope of project PLANAGEO, a geophysical survey using the time domain electromagnetic (TDEM) method was planned and conducted. This survey aimed to contribute to the hydrogeological conceptual model of the KOS and KOH aquifer systems, to validate the 1960 data electrical resistivity reprocessing and to define the future location of deep boreholes. The TDEM survey allowed identifying different layers with different geoelectric characteristics and assigning electrical resistivity characteristics to each hydrogeological feature of the aquifer systems. These assumptions were found adequate, and the results were used to define the drilling locations of 5 wells.